Optimizing Scholarship Recipient Selection in Vocational High Schools: A Strategic Approach with the Simple Additive Weighting (SAW) Method - Rahmatia Wulan Dari; Ilmawati; Yesri Elva (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study aims to address issues in the scholarship recipient selection process in vocational high schools (SMK). The main challenge lies in the limited availability of scholarship, necessitating careful selection. The objective of this study is to implement the Simple Additive Weighting (SAW) method as a solution to enhance the structure, efficiency, and objectivity of the selection process. The SAW method is used as the primary approach, which involves steps such as determining the criteria, assigning preference weights, and ranking alternatives. The data used included a sample of five scholarship candidates from SMK N 1 Hiliran Gumanti, with the criteria divided into benefits and costs. The results of the selection of scholarships demonstrate the success of SAW in providing rankings according to predefined criteria. This research highlights the effectiveness of the SAW method in delivering objective rankings to scholarship candidates. The final results can help the selection team to determine the best scholarship recipients. The implementation of SAW is expected to create a more structured and efficient selection system at the SMK, opening opportunities for improved educational access for financially needy students.